Exploring the Determinants of Agritourism Business Owners’ Expansion Intention - Lauren Collins; Nellie Hill-Sullins; Jason Ellis Ph.D.; Raluca Cozma (Journal of Applied Communications, 2024)
The purpose of this study was to identify the determinants informing Kansas agritourism owners’ intention to expand their business guided by the Theory of Planned Behavior. Agritourism can bring economic, environmental, and social benefits to agricultural and community systems. To realize these benefits, agritourism business owners need related goals, community support, and a multi-modal communications effort. A quantitative, descriptive survey research design was used to gather data from businesses registered with the Kansas Agritourism Program. Results showed agritourism operators' attitudes, perceived behavioral control, and subjective norms were positively and significantly correlated with, and predictive of, their intention to expand their business. Attitudes were measured by goals for the business, of which capturing new customers was the most important. Subjective norms were measured by community perception of the agritourism businesses’ local contribution, of which contributing to the growth and success of the local economy was the most prominent. Perceived behavioral control was measured by barriers to expansion, of which deciding how to promote the business to target customers was the biggest problem. The importance and number of communication channels used were also positively and significantly correlated with agritourism business owners’ intention to expand their business. The most important communication channels for agritourism promotion were word-of-mouth and Facebook. Future research needs include a richer understanding of these findings through qualitative analysis. Practitioners should address agritourism operators’ goal of targeting new customers and barriers to effectively promoting to them by providing tailored trainings and resources for strategic communication.
Keywords: Theory of Planned Behavior; promotion; tourism; agribusiness development